Pengaruh Sales growth, Capital intensity, Kompensasi Eksekutif, dan Kepemilikan Manajerial Terhadap Penghindaran Pajak - Achmad Juniawan Hendrianto; Suripto; Effriyanti; Wahyu Nurul Hidayati (Owner : Riset dan Jurnal Akuntansi, 2022)
The slowdown in tax revenues was influenced by national economic conditions that were under pressure due to the weakening of the manufacturing industry, a decrease in international trade activities, and restrictions on community activities due to the pandemic. The objectives of this article is to find out how much sales growth, capital intensity, executive compensation, and manager ownership affect taxation. This is a form of quantitative associative research, with secondary data from annual financial statements served as the data source. The population includes property companies listed on the Indonesia Stock Exchange in 2017-2020 with a total population of 65 companies. The sample selection method chosen was purposive sampling and samples that matched the criteria obtained by 11 companies with a period of 4 years, so that 44 observation data were obtained. The data analysis methods used are descriptive statistics, testing classical assumptions, regression of panel data and hypothesis testing. Data analysis of this study uses statistical calculations using the Eviews application version 12. The results of simultaneous research (statistical test F) show that Sales growth, Capital intensity, Executive Compensation, and Managerial Ownership together affect tax avoidance. Based on the results of partial research (statistical test t) shows that Sales growth and Capital intensity have a negative and significant effect on tax avoidance, while in Executive Compensation and Managerial Ownership do not have a significant effect on tax avoidance.